2005
DOI: 10.1038/labinvest.3700250
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in transcription clusters underlie development of bladder cancer along papillary and nonpapillary pathways

Abstract: Bladder cancer develops in the urothelial lining from intraurothelial preneoplasia via two pathways, papillary and nonpapillary, which correspond to nonaggressive and aggressive forms of the disease. Because these two forms of cancer may develop via distinct molecular events, we examined the gene expression patterns in the development of bladder cancer from preneoplasia along papillary and nonpapillary pathways. The expression profiles of 19 pairs of RNA samples from adjacent urothelium and tumors were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…In some aggressive tumors, collagen type I is overexpressed and plays a role in tumor development (Yang et al, 2007;Liang et al, 2008). Overexpression of FN1 has been found to correlate with a high histologic grade and an invasive phenotype (Kim et al, 2005). Niu et al (2009) also identified differences in FN1 expression between superficial bladder transitional cell carcinoma and normal urothelial cells.…”
Section: Discussionmentioning
confidence: 94%
“…In some aggressive tumors, collagen type I is overexpressed and plays a role in tumor development (Yang et al, 2007;Liang et al, 2008). Overexpression of FN1 has been found to correlate with a high histologic grade and an invasive phenotype (Kim et al, 2005). Niu et al (2009) also identified differences in FN1 expression between superficial bladder transitional cell carcinoma and normal urothelial cells.…”
Section: Discussionmentioning
confidence: 94%
“…27 The primer sequences used are described in supplemental Methods. To avoid amplification of genomic DNA, each gene primer was chosen from different exons.…”
Section: Transcription Analysismentioning
confidence: 99%
“…Microarray analyses have not only delineated gene expression profiles distinct for different histological subtypes (Thykjaer et al, 2001;Dyrskjt et al, 2003Dyrskjt et al, , 2004Sanchez-Carbayo et al, 2003;Blaveri et al, 2005;Wild et al, 2005), but also gene expression signatures of importance for tumor recurrence and progression (Dyrskjt et al, 2003(Dyrskjt et al, , 2005Modlich et al, 2004;Wild et al, 2005), and patient survival (Blaveri et al, 2005;Kim et al, 2005). Whereas previous microarray studies of bladder cancer mostly have been dedicated to isolate gene expression profiles and predictors that classify tumors according to stage, recurrence and outcome, we focus on a comprehensive molecular characterization of Ta and T1 tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, genome-wide expression profiling by the use of microarray technology has contributed to extensive and new insights into the complex gene expression patterns and dysregulation of genes occurring in urothelial neoplasias (Thykjaer et al, 2001;Dyrskjt et al, 2003Dyrskjt et al, , 2004Dyrskjt et al, , 2005Mor et al, 2003;SanchezCarbayo et al, 2003;Modlich et al, 2004;Blaveri et al, 2005;Kim et al, 2005;Wild et al, 2005). Microarray analyses have not only delineated gene expression profiles distinct for different histological subtypes (Thykjaer et al, 2001;Dyrskjt et al, 2003Dyrskjt et al, , 2004Sanchez-Carbayo et al, 2003;Blaveri et al, 2005;Wild et al, 2005), but also gene expression signatures of importance for tumor recurrence and progression (Dyrskjt et al, 2003(Dyrskjt et al, , 2005Modlich et al, 2004;Wild et al, 2005), and patient survival (Blaveri et al, 2005;Kim et al, 2005).…”
Section: Introductionmentioning
confidence: 99%